The Impact of Socio-economic Variables on Sustainable Family Behavior: A Case Study of the City of Irbid, Jordan - Al-Rifai, Areej Abdullah (Dirasat: Human and Social Sciences, 2024)
Objective: This study aimed to analyze family members’ attitudes on electricity and water use, as well as household solid waste generation. This study explicitly tries to correlate the amount of this behavior with social and economic characteristics such as gender, age, education level, occupation of the head of the family, family income, ownership, and type of family home. Methods: This study’s analysis was based on 340 questionnaires issued to family heads in Irbid. Using the Statistical Package for the Social Sciences (SPSS), data were evaluated by comparing the arithmetic means derived for the scale, its dimensions, and their paragraphs to the theoretical arithmetic means, whose value was (3) for each. It is deemed high if the given arithmetic mean is statistically and significantly more significant than the theoretical arithmetic mean. If the specified arithmetic mean is lower with a statistically insignificant difference, it is called a moderate level. It is deemed low if it is lower with statistical significance. Results: Based on the t-test results, it appears that families in Irbid city are utilizing resources sustainably. Sustainable practices are prioritized for power and water usage, while solid waste management ranked third in terms of sustainability. The average level of sustainable consumption behavior among Irbid city families also showed notable variations, which may be attributed to social and economic factors considered by household heads. Conclusions: More research should focus on sustainable household behavior and the associated economic and social variables, starting with the idea that household consumption patterns are crucial to understanding, evaluating, and mitigating environmental stress at the urban level.